Hematologic Toxicities of Chemotherapy in Lung Cancer Patients: A Retrospective Study in Dr. M. Djamil Hospital Padang, Indonesia - Yori Yuliandra; Hansen Nasif; Sabrina Ermayanti; Lilik Sulistyowati; Dian A. Juwita (Indonesian Journal of Clinical Pharmacy, 2019)
The use of chemotherapeutic agents in the management of cancer is often followed by a range of toxicities to various organ systems. A retrospective study on the hematologic toxicities of chemotherapy in lung cancer patients has been carried out. The study was conducted by a cross-sectional method from medical records of four-year data in 2010–2014 at Dr. M. Djamil Hospital Padang, West Sumatra, Indonesia. Data from medical records of patients diagnosed with lung cancer and underwent chemotherapy, not suffering from primary hematologic diseases, and with normal kidney and liver function prior to chemotherapy were studied. A number of 22 medical records of lung cancer patients which met the criteria with a total of 40 chemotherapy cycles were observed. The study revealed that a combination of carboplatin-paclitaxel was the most common chemotherapy used for the patients (72.7%). The hematologic toxicities comprised anemia, leukopenia, and thrombocytopenia with the severity ranging from grade 1–3. Carboplatin-paclitaxel was the only combination that caused these three toxicities, and the only combination to cause thrombocytopenia as well. Anemia was the major hematologic toxicity experienced by more than half of the patients. The study concludes that there is a reasonably high incidence of hematologic toxicities from chemotherapy among lung cancer patients.Keywords: Anemia, chemotherapy, hematologic toxicity, leukopenia, lung cancer, thrombocytopenia Toksisitas Hematologis Akibat Kemoterapi pada Pasien Kanker Paru: Studi Retrospektif di RSUP Dr. M. Djamil PadangAbstrak Penggunaan obat kemoterapi dalam pengobatan kanker sering disertai dengan toksisitas pada beberapa sistem organ. Kajian retrospektif terhadap toksisitas hematologis akibat kemoterapi pada pasien kanker paru sudah dilaksanakan. Studi ini dilaksanakan dengan metode cross-sectional dari data rekam tahun 2010–2014 di RSUP Dr. M. Djamil Padang, Sumatera Barat. Data pasien yang didiagnosis menderita kanker paru yang menjalani kemoterapi, tidak menderita penyakit hematologis dan gangguan hematopoiesis, serta memiliki fungsi ginjal dan hati yang normal dimasukkan ke dalam kajian. Sejumlah 22 pasien memenuhi kriteria dengan jumlah siklus kemoterapi sebanyak 40. Hasil kajian ini mengungkap bahwa kombinasi karboplatin-paklitaksel merupakan kemoterapi yang paling banyak digunakan (72,2%). Toksisitas hematologis yang terjadi meliputi anemia, leukopenia, dan trombositopenia dengan tingkat keparahan 1–3. Karboplatin-paklitaksel merupakan satu-satunya kombinasi kemoterapi yang menyebabkan ketiga toksisitas hematologis tersebut, sekaligus juga merupakan satu-satunya kombinasi yang menimbulkan trombositopenia. Anemia merupakan toksisitas hematologis yang paling banyak terjadi meliputi lebih dari separuh pasien. Penelitian ini menyimpulkan bahwa terdapat toksisitas hematologis yang cukup tinggi akibat kemoterapi pada pasien kanker paru.Kata kunci: Anemia, kanker paru, kemoterapi, leukopenia, toksisitas hematologis, trombositopenia